A method to improve the superconducting core density and J of iron-based superconducting tapes c Method

CN122907435APending Publication Date: 2026-10-13INST OF ELECTRICAL ENG CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611246125.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

122系铁基超导体Tc为38 K,Hc2可超过100 T,更重要的是其各向异性较低(1~2),且晶界弱连接效应不明显

Benefits of technology

[0029](1)本发明在现有铜/银复合包套122系铁基超导带材制备方法的基础上,仅对二次管(外包套)的参数进行限定,同时对工艺进行适当的调整,即可提升铁基超导带材超导芯的致密度,进而提升其临界电流密度Jc。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a method for improving the density and J c of an iron-based superconducting tape superconducting core, and belongs to the technical field of superconducting materials. The method comprises adjusting the material of a secondary tube used in a powder-in-tube method and adjusting cold deformation process parameters according to the material of the secondary tube; wherein the processing state tensile strength of the secondary tube is greater than 420 MPa and less than 800 MPa; and adjusting the cold deformation process parameters specifically comprises reducing corresponding parameters of drawing treatment and rolling treatment. On the basis of an existing copper / silver composite sheath 122 system iron-based superconducting tape preparation method, only the parameters of the secondary tube are limited, and the process is properly adjusted, so that the density of the iron-based superconducting tape superconducting core is improved, and then the critical current density J c is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of superconducting materials technology, and particularly relates to a method for improving the superconducting core density and J of iron-based superconducting tapes. c The method. Background Technology

[0002] In 2008, Hosono's research group at the Tokyo Institute of Technology in Japan discovered LaFeAsO₂. 1-x F x It has a critical transition temperature of 26 K (T c Following this, a series of iron-based superconductors (IBS) with different structures were discovered. IBS not only... c High, and also has a high upper critical field (H c2 Its advantages, such as low anisotropy (γ), make it a promising candidate for high-field applications in fields such as nuclear magnetic resonance imaging (MRI), nuclear magnetic resonance spectrometers (NMR), superconducting energy storage systems (SMES), and high-energy physics accelerators.

[0003] Iron-based superconductors are mainly classified into four systems: 1111-type REFeAsO, 111-type LiFeAs, 122-type AEFe2As2, and 11-type FeSe. Among them, the 122-type iron-based superconductors have the greatest potential for practical application. (The text then abruptly shifts to a seemingly unrelated topic: 122-type iron-based superconductors T...) c 38 K, H c2 It can exceed 100 T, and more importantly, it has low anisotropy (1-2) and the weak grain boundary connectivity effect is not obvious. Currently, the critical current density J of 122 series iron-based superconducting wire and strip materials is being increased. c The methods include the following: (1) optimization of preparation process; (2) chemical element doping and element addition; (3) introduction of artificial pinning centers; (4) grain boundary engineering.

[0004] Although various methods have been developed to increase the critical current density J of superconducting wires and strips, c However, developing new methods to increase the critical current density of 122 series iron-based superconducting wire and strip materials is not feasible. c This method is one of the ways to make 122 series iron-based superconducting tapes practical. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a method for improving the superconducting core density and J0 of iron-based superconducting tapes. c This method increases the density of the superconducting core in iron-based superconducting tapes, thereby improving the critical current density J. c .

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A method to improve the superconducting core density and J of iron-based superconducting tapes c The method includes adjusting the material of the secondary tube used in the powder packing method and adjusting the cold deformation process parameters according to the material of the secondary tube.

[0008] Among them, the tensile strength of the secondary tube in the processing state is greater than 420MPa and less than 800MPa;

[0009] Adjusting the cold deformation process parameters specifically includes reducing the corresponding parameters for drawing and rolling processes.

[0010] The secondary tube has a tensile strength greater than 240 MPa when annealed at 740°C.

[0011] The conductivity of the secondary tube is greater than 5.8 MS / m;

[0012] And / or, the thermal conductivity of the secondary tube at 20°C is greater than 30 W / (m·K).

[0013] The secondary tube is made of copper alloy.

[0014] The secondary tube is made of chromium zirconium copper, beryllium bronze, or iron white copper.

[0015] Among them, the iron-based superconducting tape is the 122 series iron-based superconducting tape.

[0016] The method includes the following steps:

[0017] S1: The iron-based superconducting precursor powder is loaded into the primary tube and sealed at both ends. The primary tube is a silver tube.

[0018] S2: The silver tube obtained in step S1 is drawn and then cut to obtain several single cores;

[0019] S3: Insert the single core into the secondary tube and seal both ends;

[0020] S4: Perform a pulling process on the secondary tube sample obtained in step S3;

[0021] S5: Roll the drawn sample obtained in step S4 to obtain a rolled sample;

[0022] S6: The rolled sample is sintered to obtain iron-based superconducting tape.

[0023] Specifically, based on the tensile strength of pure copper in the processing state, for every 10% increase in the tensile strength of the secondary tube in the processing state, the thickness of the secondary tube used in step S3 is reduced by 5%; wherein the percentage increase in the tensile strength of the secondary tube in the processing state is rounded down.

[0024] Specifically, based on the tensile strength of pure copper in the processing state, for every 10% increase in the tensile strength of the secondary tube in the processing state, the area reduction rate and drawing speed of a single drawing in step S4 are both reduced by 5%; wherein the percentage increase in the tensile strength of the secondary tube in the processing state is rounded down.

[0025] Specifically, based on the tensile strength of pure copper in the processing state, for every 10% increase in the tensile strength of the secondary tube in the processing state, the rolling pressure and rolling speed of a single rolling process in step S5 are reduced by 10%; wherein the percentage increase in the tensile strength of the secondary tube in the processing state is rounded down.

[0026] The formula for calculating the percentage increase in the tensile strength of the secondary tube under processing conditions is as follows: .

[0027] The above rounding down means that, based on the tensile strength of pure copper in the working state, if the calculated percentage increase in the tensile strength of the secondary tube in the working state is 5%, then it is calculated as 0, that is, the thickness of the secondary tube does not change; if the calculated percentage increase in the tensile strength of the secondary tube in the working state is 12%, then it is calculated as 10%, that is, the thickness of the secondary tube is reduced by 5%.

[0028] The beneficial effects of this invention are as follows:

[0029] (1) Based on the existing method for preparing copper / silver composite-clad 122 series iron-based superconducting tapes, this invention only limits the parameters of the secondary tube (outer cladding) and makes appropriate adjustments to the process, thereby improving the density of the superconducting core of the iron-based superconducting tape and thus increasing its critical current density J. c .

[0030] (2) The present invention further adjusts the cold deformation parameters in the preparation method, which can further improve its critical current density J. c .

[0031] (3) The strip treated by the method of the present invention has better mechanical properties and is less prone to deformation and damage during actual use. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0033] The commonly used preparation method for 122-series iron-based superconductors is the powder-in-tube method (PIT). In the PIT method, 122-series iron-based superconducting tapes typically use silver as a cladding to prevent reaction with the superconducting core, resulting in high preparation costs. Therefore, copper / silver composite cladding with an inner silver layer and an outer copper layer is now frequently used.

[0034] The inventors discovered that the secondary tube of currently commonly manufactured copper / silver composite-clad 122-series iron-based superconducting tapes is made of pure copper. While this significantly reduces the manufacturing cost, it presents two problems. First, copper's hardness is only slightly higher than silver's. When using a copper / silver composite cladding, the low-melting-point eutectic relationship between the two at 750℃ limits the final heat treatment temperature of the tape, resulting in a lower critical current density for the copper / silver composite-clad tape compared to the silver-clad tape. Second, due to the lower annealing temperature of pure copper, the mechanical properties of the copper / silver composite-clad tape are lower after heat treatment, and it may experience deformation and damage similar to that of the silver-clad tape in practical applications.

[0035] Based on the above findings, the inventors believe that improving the material of the secondary tube will increase the critical current density of the 122 series iron-based superconducting tape. c One approach is to prepare composite sheathed strips using the powder-packing method. Loose superconducting precursor powder is packed into a primary tube (silver tube), then forged and drawn to a specific size to obtain a single core. This single core is then packed into a secondary tube, and cold deformation processes such as forging and drawing continuously reduce the diameter of the composite sheath, leading to continuous densification of the superconducting precursor powder. Finally, rolling is performed to create texture and further increase density. The inventors discovered that the higher the tensile strength of the secondary tube, the more significant the powder densification effect. Therefore, using a higher-strength secondary tube yields a higher-density superconducting core, resulting in a higher critical current density after heat treatment. Simultaneously, when the annealing temperature of the secondary tube is higher than the heat treatment temperature of the strip, the work hardening generated during cold deformation is preserved, resulting in stronger mechanical properties of the strip after heat treatment and making it less prone to deformation damage during use. However, excessively high secondary tube strength can lead to a mismatch between the deformation of the secondary tube and the primary tube, causing uneven deformation or even damage to the superconducting core during rolling. Furthermore, the material of the secondary tube also affects the heat exchange between the superconducting core and the low-temperature environment and plays a role in sharing current transmission, requiring good thermal conductivity and electrical conductivity. In summary, the selection of the secondary tube requires appropriate strength and a high annealing temperature, while also considering both thermal conductivity and electrical conductivity.

[0036] Based on the above research and experimental verification, the material requirements for the secondary tube are as follows: the tensile strength of the secondary tube in the processed state is greater than 420 MPa and less than 800 MPa; the tensile strength of the secondary tube after annealing at 740℃ is greater than 240 MPa; the electrical conductivity of the secondary tube is greater than 5.8 MS / m; and the thermal conductivity of the secondary tube at 20℃ is greater than 30 W / (m·K). Experimental verification shows that copper alloys with a tensile strength greater than 800 MPa are not suitable for rolling together with pure silver primary tubes as secondary tubes, as this will result in severe deformation mismatch due to excessive differences in the strength of the inner and outer sheaths. An electrical conductivity of 5.8 MS / m corresponds to 10% IACS; values ​​lower than this are not conducive to practical applications.

[0037] A survey of existing materials revealed that most copper alloys meet the requirements for use as secondary tubes.

[0038] Table 1. Comparison of strength, electrical conductivity, and thermal conductivity of copper alloys with other metallic materials.

[0039]

[0040] As shown in Table 1, copper alloys such as chromium-zirconium copper, iron-copper alloys, and beryllium bronze exhibit higher tensile strength in the processed state than pure copper. Therefore, this is beneficial for powder densification during cold deformation, resulting in a higher density superconducting core. Furthermore, compared to stainless steel and other metals, copper alloys have moderate hardness and excellent machinability, facilitating cold deformation processes such as drawing and rolling. In addition, the tensile strength of annealed copper alloys is also higher than that of pure copper, and the heat-treated strip maintains good mechanical strength. Finally, the electrical and thermal conductivity of copper alloys is significantly higher than that of stainless steel and other metals. Therefore, copper alloys are more suitable as materials for secondary tubes in composite-clad iron-based superconducting strips, not only improving the density of the superconducting core to increase the critical current density but also facilitating processing and practical applications.

[0041] Furthermore, this invention adjusts the cold deformation process; the adjustment is based on the existing common cold deformation process for copper / silver composite sheathed strips, and includes the following three aspects:

[0042] 1) Secondary tube thickness: Based on the maximum tensile strength of cold-worked pure copper of 420MPa, when the tensile strength of the copper alloy secondary tube in the cold-worked state increases by 10%, the thickness of the secondary tube decreases by 5%. Any increase of less than 10% is not included in the adjustment.

[0043] 2) Drawing process: Based on the maximum tensile strength of cold-worked pure copper of 420MPa, when the tensile strength of the copper alloy secondary tube used increases by 10% in the cold-worked state, the surface reduction rate of single deformation and the drawing speed are reduced by 5%. The portion of the increase of less than 10% is not included in the adjustment.

[0044] 3) Rolling process: Based on the maximum tensile strength of cold-worked pure copper of 420MPa, when the tensile strength of the copper alloy secondary tube used increases by 10% in the cold-worked state, the amount of pressure and rolling speed of single deformation are reduced by 10%, and the part with an increase of less than 10% is not included in the adjustment.

[0045] Example 1:

[0046] A method to improve the superconducting core density and J of iron-based superconducting tapes c In this embodiment, the secondary tube is made of chromium-zirconium copper, specifically using a chromium-zirconium copper / silver composite sheath. The method specifically includes the following steps:

[0047] S1: Load 122 series iron-based superconducting precursor powder into a silver tube (primary tube) with an outer diameter of 10 mm and an inner diameter of 8 mm, and seal both ends.

[0048] S2: Use a carbide die to draw the silver tube to a diameter of 5.33mm, and then cut it into 7 single cores of the same length.

[0049] S3: Insert 7 single cores into a chromium zirconium copper C18150 tube (secondary tube, cold-worked tensile strength 450MPa, tensile strength increased by 7%, sheath thickness does not need to be adjusted) with an outer diameter of 20mm and an inner diameter of 16mm, and seal both ends.

[0050] S4: The secondary tube sample was drawn using a carbide mold to obtain a 7-core round wire. The single drawing surface reduction rate was 12%, and the drawing speed was 3m / min (the drawing surface reduction rate and drawing speed do not need to be adjusted). After several drawing operations, the final diameter was 1.7mm.

[0051] S5: The 7-core round wire with a diameter of 1.7mm is subjected to flat roll rolling. The single rolling pressure is 31% and the rolling speed is 2m / min (the rolling pressure and rolling speed do not need to be adjusted). The thickness of the final rolled sample is 0.4mm.

[0052] S6: A rolled sample with a thickness of 0.4 mm was sintered at 740℃ for 5 hours. After sintering, it was cooled in the furnace to obtain an iron-based superconducting 7-core strip.

[0053] Example 2:

[0054] A method to improve the superconducting core density and J of iron-based superconducting tapes c In this embodiment, the secondary tube is made of beryllium bronze, specifically a beryllium bronze / silver composite sheath. The method specifically includes the following steps:

[0055] S1: Load 122 series iron-based superconducting precursor powder into a silver tube (primary tube) with an outer diameter of 10 mm and an inner diameter of 8 mm, and seal both ends.

[0056] S2: Use a carbide die to draw the silver tube to a diameter of 5.33mm, and then cut it into 7 single cores of the same length.

[0057] S3: Insert 7 single cores into a beryllium bronze C17500 (secondary tube, cold-worked tensile strength 510MPa, tensile strength increased by 21%, sheath thickness reduced by 10%) with an outer diameter of 19.6mm and an inner diameter of 16mm, and seal both ends.

[0058] S4: The secondary tube sample was drawn using a carbide die to obtain a 7-core round wire. The single drawing surface reduction rate was 10.8%, and the drawing speed was 2.7 m / min (the drawing surface reduction rate and drawing speed were reduced by 10%). After several drawing operations, the final diameter was 1.7 mm.

[0059] S5: The 7-core round wire with a diameter of 1.7mm is subjected to flat roll rolling. The single rolling reduction is 24.8%, and the rolling speed is 1.6m / min (the rolling reduction and rolling speed are reduced by 20%). The thickness of the final rolled sample is 0.4mm.

[0060] S6: A rolled sample with a thickness of 0.4 mm was sintered at 740℃ for 5 hours. After sintering, it was cooled in the furnace to obtain an iron-based superconducting 7-core strip.

[0061] Example 3:

[0062] A method to improve the superconducting core density and J of iron-based superconducting tapes c In this embodiment, the secondary tube is made of white copper-iron alloy, specifically using a white copper-iron / silver composite sheath. The method specifically includes the following steps:

[0063] S1: Load 122 series iron-based superconducting precursor powder into a silver tube (primary tube) with an outer diameter of 10 mm and an inner diameter of 8 mm, and seal both ends.

[0064] S2: Use a carbide die to draw the silver tube to a diameter of 5.33mm, and then cut it into 7 single cores of the same length.

[0065] S3: Insert 7 single cores into a 19mm outer diameter, 16mm inner diameter iron-white copper T70600 (secondary tube, cold-worked tensile strength 650MPa, tensile strength increased by 54.7%, sheath thickness reduced by 25%), and seal both ends.

[0066] S4: The secondary tube sample was drawn using a carbide die to obtain a 7-core round wire. The surface reduction rate of a single drawing was 9%, and the drawing speed was 2.25 m / min (the surface reduction rate and drawing speed were reduced by 25%). After several drawing operations, the final diameter was 1.7 mm.

[0067] S5: A 7-core round wire with a diameter of 1.7 mm is rolled with flat rolls. The single rolling pressure is 15.5%, and the rolling speed is 1 m / min (the rolling pressure and rolling speed are reduced by 50%). The thickness of the final rolled sample is 0.4 mm.

[0068] S6: A rolled sample with a thickness of 0.4 mm was sintered at 740℃ for 5 hours. After sintering, it was cooled in the furnace to obtain an iron-based superconducting 7-core strip.

[0069] Comparative Example 1:

[0070] In Comparative Example 1, the secondary tube is made of copper, specifically using a copper / silver composite sheath. Comparative Example 1 includes the following steps:

[0071] S1: Load 122 series iron-based superconducting precursor powder into a silver tube (primary tube) with an outer diameter of 10 mm and an inner diameter of 8 mm, and seal both ends.

[0072] S2: Use a carbide die to draw the silver tube to a diameter of 5.33mm, and then cut it into 7 single cores of the same length.

[0073] S3: Insert 7 single cores into a pure copper tube (secondary tube, cold-worked tensile strength 420MPa) with an outer diameter of 20mm and an inner diameter of 16mm, and seal both ends.

[0074] S4: The secondary tube sample was drawn using a carbide die to obtain a 7-core round wire. The surface reduction rate of a single drawing was 12%, the drawing speed was 3m / min, and the final diameter was 1.7mm after several drawing operations.

[0075] S5: 7-core round wire with a diameter of 1.7mm is rolled by flat rolls with a single rolling reduction of 31% and a rolling speed of 2m / min, resulting in a final strip thickness of 0.4mm.

[0076] S6: Sinter a 0.4mm thick strip at 740℃ for 5 hours, and then cool it in the furnace after sintering.

[0077] The iron-based superconducting tapes obtained in Examples 1 to 3 and Comparative Example 1 were tested, and the results are shown in Table 2.

[0078] Table 2. Superconducting core hardness and critical current density of the superconducting tapes in each embodiment.

[0079]

[0080] The test results from Example 1 and Comparative Example 1 show that using chromium-zirconium copper as the secondary tube did not significantly improve the hardness of the secondary tube after cold working. Therefore, the hardness of the superconducting core was not improved, and the goal of improving the density of the superconducting core was not achieved. Thus, in Example 1, J... cNo improvement was achieved. However, due to the higher annealing temperature of chromium-zirconium copper, the hardness of the secondary tube decreased less after sintering at 740℃ than that of pure copper, thus achieving the goal of improving mechanical properties. The test results from Examples 2, 3, and Comparative Example 1 show that as the hardness of the secondary tube increases after cold working, the hardness of the superconducting core also increases, indicating a continuous increase in the density of the superconducting core, thereby increasing the critical current density. Simultaneously, the higher annealing temperature also allows the heat-treated strip to maintain higher hardness, significantly improving the mechanical properties of the strip.

[0081] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention. The above embodiments are provided only for the purpose of describing the present invention and are not intended to limit the present invention. Parts not described in detail in this specification are well-known in the art and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. All equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be covered within the scope of the present invention.

Claims

1. A method for improving the superconducting core density and J of iron-based superconducting tapes c The method is characterized by, The method includes adjusting the material of the secondary tube used in the powder packing method and adjusting the cold deformation process parameters according to the material of the secondary tube; Among them, the tensile strength of the secondary tube in the processing state is greater than 420MPa and less than 800MPa; Adjusting the cold deformation process parameters specifically includes reducing the corresponding parameters for drawing and rolling processes.

2. The method for improving the superconducting core density and J of iron-based superconducting tapes according to claim 1. c The method is characterized by, The secondary tube has a tensile strength greater than 240 MPa when annealed at 740℃.

3. The method for improving the superconducting core density and J of iron-based superconducting tapes according to claim 1. c The method is characterized by, The conductivity of the secondary tube is greater than 5.8 MS / m; And / or, the thermal conductivity of the secondary tube at 20°C is greater than 30 W / (m·K).

4. The method for improving the superconducting core density and J of iron-based superconducting tapes according to claim 1. c The method is characterized by, The secondary tube is made of copper alloy.

5. The method for improving the superconducting core density and J of iron-based superconducting tapes according to claim 4. c The method is characterized by, The secondary tube is made of chromium zirconium copper, beryllium bronze, or iron white copper.

6. The method for improving the superconducting core density and J of iron-based superconducting tapes according to claim 1 c The method is characterized by, The iron-based superconducting tape is a 122 series iron-based superconducting tape.

7. The method for improving the superconducting core density and J of iron-based superconducting tapes according to any one of claims 1 to 6. c The method is characterized by, The method includes the following steps: S1: The iron-based superconducting precursor powder is loaded into the primary tube and sealed at both ends. The primary tube is a silver tube. S2: The silver tube obtained in step S1 is drawn and then cut to obtain several single cores; S3: Insert the single core into the secondary tube and seal both ends; S4: Perform a pulling process on the secondary tube sample obtained in step S3; S5: Roll the drawn sample obtained in step S4 to obtain a rolled sample; S6: The rolled sample is sintered to obtain iron-based superconducting tape.

8. The method for improving the superconducting core density and J of iron-based superconducting tapes according to claim 7. c The method is characterized by, Based on the tensile strength of pure copper in the processing state, for every 10% increase in the tensile strength of the secondary tube in the processing state, the thickness of the secondary tube used in step S3 is reduced by 5%; wherein the percentage increase in the tensile strength of the secondary tube in the processing state is rounded down.

9. The method for improving the superconducting core density and J of iron-based superconducting tapes according to claim 7. c The method is characterized by, Based on the tensile strength of pure copper in the working state, for every 10% increase in the tensile strength of the secondary tube in the working state, the area reduction rate and drawing speed of the single drawing process in step S4 are reduced by 5%; wherein the percentage increase in the tensile strength of the secondary tube in the working state is rounded down.

10. The method for improving the superconducting core density and J of iron-based superconducting tapes according to claim 7. c The method is characterized by, Based on the tensile strength of pure copper in the working state, for every 10% increase in the tensile strength of the secondary tube in the working state, the rolling pressure and rolling speed of the single rolling process in step S5 are reduced by 10%; wherein the percentage increase in the tensile strength of the secondary tube in the working state is rounded down.